Teleconnection Between Early Winter Monsoon System and Harmful Algal Blooms in Shallow Lake Taihu - Jingyi Li; Boqiang Qin; Justin D. Brookes; Kun Shi; Jianming Deng; Jian Zhou; Yang Wu (Water Resources Research)
Abstract There is a long history of observation and monitoring at local scales with a focus on meteorological modulation of lakes, however, the features at the local scale are heavily influenced by large‐scale atmospheric circulation. Harmful algal blooms (HABs) in large shallow eutrophic lakes are susceptible to local meteorological conditions, but their response to climate system variability is rarely considered. This study reveals that HABs in Lake Taihu, the third largest freshwater lake in subtropical China, are promoted by the weakened East Asian monsoon system in precursory early winter, but show no response in late winter with the low temperature unfavorable for algal metabolism. The weak early winter monsoon system is characterized as the northward‐shifted polar front jet and eastward‐tilted East Asian Trough. The accompanied anomalous descending motion decelerates surface winds over the middle to lower reaches of the Yangtze River including Taihu basin by strengthening atmospheric stratification and decreasing turbulent activity in the lower troposphere. The weakened surface winds reduce sediment resuspension and improve underwater light availability in Lake Taihu, providing favorable light condition for phytoplankton growth. It is indicated that the early‐winter surface winds rather than simultaneous nutrient supply, play a dominant role on the interannual variability of algal biomass in Lake Taihu. The positive algal biomass anomaly in early winter tends to persist and promote HABs in the following warmer seasons. Our finding validates the interannual teleconnection between climate system and HAB variation in Lake Taihu, and provides insights on predicting HABs in subtropical East Asian shallow lakes.